Formation of Uniform FeP Hollow Microspheres Assembled by Nanosheets for Efficient Hydrogen Evolution Reaction. Issue 8 (31st May 2017) - Guo, Xiaosong; Feng, Zijia; Lv, Zezhong; Bu, Yufan; Liu, Qiulin; Zhao, Longqing; Hao, Chuncheng; Li, Guicun; Lei, Qingquan
Abstract: High‐performance electrocatalysts with superior stability are critically important for their practical applications in the hydrogen evolution reaction (HER). Recently, some electrocatalysts with hollow and porous structures have attracted much attention because of their large surface‐to‐volume ratio and highly exposed active edge sites. In this study, the hierarchical Fe‐based glycolate hollow microspheres composed of nanosheet subunits are synthesized by the solvothermal method. The morphology and microstructure of Fe‐based glycolate hollow microspheres can be controlled by adjusting the amount of ethylenediamine. After phosphorizing in nitrogen, the Fe‐based glycolate can be converted into FeP with well‐retained structure. Furthermore, the hierarchical FeP hollow microspheres have been used as electrocatalysts for HER. Benefitting from its high surface area, the FeP hollow microspheres exhibited high catalytic activity toward HER with low onset overpotential, small Tafel slope, and good stability under acidic conditions. The excellent catalytic activity and long‐term stability suggest promising application potential of FeP hollow microspheres in electrocatalytic hydrogen evolution. Abstract : Maintaining integrity : FeP hollow microspheres composed of nanosheet subunits were synthesized through a facile and controllable solvothermal method. The microspheres exhibit excellent catalytic activity in the hydrogen evolution reaction with low onset overpotential, small Tafel slope, and good stability under acidic conditions.